Activated carbon material as well as preparation method and application thereof
By using a high specific surface area modified activated carbon carrier and ball milling method to load Cu2+, the problems of complex preparation, high cost and limited adsorption capacity of existing ammonia adsorption materials are solved, and efficient ammonia adsorption performance is achieved.
Patent Information
- Application Number
- CN202510068572.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-11
AI Technical Summary
The existing ammonia adsorbent materials have problems such as complex preparation process, high cost and limited adsorption capacity, and it is difficult to effectively improve the utilization rate of Cu2+ and NH3 adsorption capacity at room temperature.
Modified activated carbon with a higher specific surface area is used as a carrier, and Cu2+ is loaded by acid-modified activated carbon and the ball milling method is used to form a highly dispersed Cu2+ official site to improve the NH3 adsorption performance.
The utilization rate of Cu2+ and NH3 adsorption capacity of activated carbon materials at room temperature are significantly improved, the preparation process is simplified, the cost is reduced, and the comprehensive performance of the adsorbent is improved.
Smart Images

Figure CN119588313A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of activated carbon adsorbents, and in particular to an activated carbon material and a preparation method and application thereof. Background Art
[0002] Ammonia (NH 3 ) is a colorless, toxic and corrosive gaseous pollutant. With the acceleration of industrialization, ammonia, as a toxic alkaline gas, poses a serious threat to human health and the environment. Ammonia mainly comes from agriculture, fertilizers, food and beverages, and rubber industries. Its high water solubility enables it to form salt particles, causing air pollution, and after oxidation, it generates nitric oxide, producing photochemical smog, which further affects the environment. Long-term exposure to NH 3 In the environment (≥300ppm), it can cause serious physical harm or even death. 3 Adsorbents such as metal organic frameworks, zeolites, covalent organic frameworks, organic polymers, etc. However, these materials also have their own disadvantages, including complex synthesis processes, limited resources, and poor absorption capacity. For example, the metal organic frameworks in MOFs are easily attacked by water molecules and are not suitable for application in terms of thermal and chemical stability. Zeolites have limited adsorption capacity and are difficult to regenerate.
[0003] The adsorption method has the advantages of simple operation, low cost and high efficiency, and is the most promising method. Activated carbon plays an important role in the field of environmental governance, especially in ammonia adsorption, due to its unique physical and chemical properties. Activated carbon has a high specific surface area and rich pore structure, and is a highly efficient adsorbent, but unmodified activated carbon is limited in deammoniation applications. Ammonia molecules have a small diameter and are captured by pores mainly through adsorption at room temperature, while most activated carbons have a large average pore size, resulting in weak ammonia adsorption capacity. Therefore, modifying activated carbon to improve its adsorption capacity for ammonia has become an important research direction at home and abroad.
[0004] At present, ammonia adsorption materials mainly include zeolite molecular sieves, silica gel, activated carbon, alumina, metal organic framework materials, etc. Activated carbon can be modified to obtain active sites for adsorption of specific substances, and has been widely used in the adsorption treatment of waste gas. For example, CN111821950A discloses a method for preparing deammoniated biochar, which increases the specific surface area and porosity of activated carbon by chloride activation and nitrate impregnation of grapefruit peel biochar, but it is easy to desorb, resulting in low ammonia adsorption efficiency.
[0005] In order to solve these problems, researchers are constantly exploring new modification methods. For example, CN202310031262.3 discloses a method for preparing modified activated carbon for ammonia adsorption, which obtains niobium-based solid superacid-modified activated carbon by immersion heating in an alkaline solution, immersion precipitation reaction in a mixed solution of niobium salt and urea, and roasting. This modified activated carbon has excellent ammonia adsorption performance in the temperature range of room temperature to 300°C, and is particularly suitable for the adsorption and purification of ammonia escape from industrial flue gas with a certain temperature.
[0006] At present, activated carbon adsorption materials have the problems of complex preparation process, high cost and limited adsorption capacity. Therefore, it is urgent to develop a carbon material with simple preparation method, low adsorbent manufacturing cost and higher active component utilization rate for room temperature adsorption of NH 3 . Summary of the invention
[0007] In order to solve the above technical problems, the present invention aims to provide an activated carbon material and a preparation method and use thereof. The activated carbon material of the present invention improves the Cu 2+ Utilization rate and NH 3 Adsorption capacity.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides an activated carbon material, which includes modified activated carbon and an active component loaded on the modified activated carbon, wherein the active component includes a divalent copper salt; the surface of the modified activated carbon contains a carboxyl functional group, and the specific surface area of the activated carbon material is 50 m 2 / g-550m 2 / g, for example, it can be 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g or 550m 2 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0010] The present invention uses modified activated carbon with a high specific surface area as a carrier. On the one hand, the surface of the modified activated carbon contains carboxyl functional groups, and the acidic groups can effectively adsorb NH 3 molecules; on the other hand, the modified activated carbon has a large number of porous structures that can 2+ The porous structure provides more space and sites for Cu 2+ Highly dispersed, which improves the Cu 2+ The utilization rate of highly dispersed Cu 2+ Provides abundant Lewis acid sites, which react with NH 3 The reaction finally forms a copper-ammine complex [Cu(NH 3 ) 4 ] 2+ , to achieve adsorption of NH 3 The purpose is to improve the room temperature adsorption of NH 3 ability.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, the specific surface area of the activated carbon material is 270 m 2 / g-320m 2 / g, for example, it can be 270m 2 / g, 275m 2 / g, 280m 2 / g, 285m 2 / g, 290m 2 / g, 295m 2 / g、300m 2 / g, 305m 2 / g, 310m 2 / g, 315m 2 / g or 320m 2 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0013] The specific surface area of the activated carbon material of the present invention is 270m 2 / g-320m 2 / g, with rich pore structure, which can greatly optimize Cu 2+ distribution, improve Cu 2+ Utilization rate. If the specific surface area is too small, it means that the copper source is loaded to block the activated carbon pores. 2+ Poor dispersion.
[0014] Preferably, based on the total mass of the activated carbon material as 100wt%, the mass fraction of the active component is 1wt%-5wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 3wt%-5wt%.
[0015] The active component content in the activated carbon material of the present invention is relatively low, which is because the surface of the modified activated carbon used in the present invention has a rich pore structure, and the presence of the pore structure can greatly optimize the Cu 2+ distribution, improve Cu 2+ The present invention further controls the content of the active component to be 1wt%-5wt%. The content of the active component affects the adsorption capacity of the adsorbent. If the content of the active component is too high, the excessive active component will block the pores of the activated carbon, reduce the specific surface area and pore size of the activated carbon material, and Cu 2+ The utilization rate has dropped significantly, resulting in an increase in production costs.
[0016] In a second aspect, the present invention provides a method for preparing the activated carbon material as described in the first aspect, the preparation method comprising the following steps:
[0017] The acid solution and the activated carbon are mixed to obtain modified activated carbon after reaction; the copper source and the modified activated carbon are mixed and ball-milled to obtain the activated carbon material.
[0018] The present invention adopts acid-modified activated carbon to obtain modified activated carbon with higher porosity and larger pores, which provides space for the subsequent loading of active components. At the same time, the acid solution also introduces carboxyl acid functional groups into the activated carbon, which are beneficial to the NH 3 The adsorption of activated carbon can improve the adsorption of NH 3 capacity.
[0019] The present invention uses ball milling to load the copper source onto the modified activated carbon. Compared with the traditional liquid phase impregnation method, the ball milling method has the following advantages: (1) the ball milling method is solvent-free, so the selection of reactants is not limited by solubility; (2) the ball milling method does not need to dissolve the reactants, so there is no need to add excessive amounts of other reactants in order to fully react some reactants, thereby achieving relatively accurate stoichiometry; (3) the ball milling reaction can synthesize some compounds that cannot be synthesized or have very low yields in traditional chemical synthesis methods; (4) ball milling can simplify the reaction conditions. The ball milling reaction does not require or requires a very small amount of solvent, and can achieve solvent-free chemical reaction, which has great potential in cost saving and green environmental protection. The introduction of the ball milling reaction will greatly reduce the use of solvents, thereby reducing production costs and avoiding the use of toxic solvents, which has significant economic benefits and social value; the preparation process of the present invention is simple, does not require high-temperature calcination, and has low cost.
[0020] Preferably, the mass concentration of the acid solution is 10%-40%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 20%-30%.
[0021] In the present invention, the mass concentration of the acid solution is further controlled to be 10%-40%. The concentration of the acid solution affects the specific surface area and the content of functional groups of the modified activated carbon. If the concentration of the acid solution is too low, the modification of the pore size of the activated carbon is limited; if the concentration of the acid solution is too high, the prepared activated carbon material has a low NH 3 The adsorption capacity is no longer increased.
[0022] Preferably, the ratio of the volume of the acid solution to the mass of the activated carbon is (50-200) mL:(1-5) g, for example, it can be 50 mL:1 g, 50 mL:2 g, 50 mL:4 g, 60 mL:1 g, 60 mL:2 g, 60 mL:4 g, 70 mL:2 g, 70 mL:4 g, 70 mL:5 g, 80 mL:2 g, 85 mL:4 g, 90 mL:5 g, 100 mL:3 g or 100 mL:5 g, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0023] Preferably, the acid solution comprises any one of hydrochloric acid, sulfuric acid or nitric acid or a combination of at least two thereof, typical but non-limiting combinations include a combination of hydrochloric acid and sulfuric acid, a combination of sulfuric acid and nitric acid, a combination of hydrochloric acid and nitric acid, a combination of hydrochloric acid, sulfuric acid and nitric acid, preferably nitric acid.
[0024] Preferably, the mesh size of the activated carbon is 40-60 mesh, for example, 40 mesh, 50 mesh or 60 mesh, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the reaction is carried out under stirring conditions.
[0026] Preferably, the stirring speed is 300rpm-600rpm, for example, it can be 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm or 600rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the reaction temperature is 40°C-60°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the reaction time is 12h-20h, for example, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the copper source comprises a divalent copper salt and / or a hydrate of a divalent copper salt.
[0030] Preferably, the divalent copper salt includes any one of copper chloride, copper nitrate, copper sulfate or copper acetate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of copper chloride and copper nitrate, a combination of copper nitrate and copper sulfate, a combination of copper sulfate and copper acetate, a combination of copper chloride and copper sulfate, a combination of copper nitrate, copper sulfate and copper acetate, a combination of copper chloride, copper nitrate and copper sulfate, a combination of copper chloride, copper nitrate, copper sulfate and copper acetate, preferably copper chloride.
[0031] Preferably, the ball-to-material ratio of the ball mill is 1:(1-2), for example, it can be 1:1, 1:1.5, 1:1.8 or 1:2, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the rotation speed of the ball mill is 300 rpm-500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the ball milling time is 1 h-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the diameter of the large balls used in the ball milling process is 1 cm-1.5 cm, for example, 1 cm, 1.2 cm, 1.4 cm or 1.5 cm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the diameter of the balls used in the ball milling process is 6 mm-8 mm, for example, 6 mm, 6.5 mm, 7 mm, 7.5 mm or 8 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] Preferably, the mass ratio of large balls to small balls used in the ball milling process is 1:(1-2), for example, 1:1, 1:1.5, 1:1.8 or 1:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In the ball milling process of the present invention, large-diameter ball milling balls and small-diameter ball milling balls are used in cooperation with each other for ball milling. The grinding energy generated by the large ball and the small ball during movement is different. The large ball has a large impact force and can more effectively break larger particles; the small ball can enter a narrower space and grind finer particles. The small ball has a high impact frequency and can increase the contact area with the material, achieving more frequent impact times, thereby improving the grinding effect and the fine grinding and mixing of the sample. The two kinds of balls are used in combination, and the use of balls of different sizes helps to achieve a more uniform grinding effect, reduce energy consumption and improve the efficiency of the mill. At the same time, the active component and the modified activated carbon are mixed more evenly, the dispersibility of the active component is better, the ball milling efficiency is improved, and the grinding process is optimized.
[0038] Preferably, drying is further performed after the ball milling and before obtaining the activated carbon material.
[0039] Preferably, the drying temperature is 70°C-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the drying time is 12h-24h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0042] (1) mixing nitric acid and activated carbon at a concentration of 20%-30% according to (50-200) mL: (1-5) g, reacting at 40° C.-60° C. for 12 h-20 h, filtering, washing with water until the filtrate is neutral, and drying at 70° C.-90° C. for 12 h-24 h to obtain modified activated carbon;
[0043] (2) mixing cupric chloride and modified activated carbon, ball milling at 300 rpm-500 rpm for 1 h-3 h in a ball-to-material ratio of 1:(1-2), and drying at 70° C.-90° C. for 12 h-24 h to obtain the activated carbon material.
[0044] In a third aspect, the present invention provides a use of the activated carbon material as described in the first aspect, wherein the activated carbon material is used for ammonia adsorption.
[0045] The activated carbon material provided by the present invention has excellent NH 3 The activated carbon material provided by the present invention is used for adsorbing NH 3 There are three different mechanisms: (1) NH 3 H in the water 2 O adsorption to form NH 4+ ions; (2) The surface of the modified activated carbon contains carboxyl functional groups that effectively adsorb NH 3 ; (3) Highly dispersed Cu on the surface of activated carbon material 2+ Provides abundant Lewis acid sites to adsorb NH 3 Finally, the copper-ammine complex [Cu(NH 3 ) 4 ] 2+ .
[0046] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0047] Compared with the prior art, the present invention has at least the following beneficial effects:
[0048] (1) The present invention uses modified activated carbon with a high specific surface area as a carrier. On the one hand, the surface of the modified activated carbon contains carboxyl functional groups, which can effectively adsorb NH 3 molecules; on the other hand, the modified activated carbon has a porous structure and can 2+ The loading provides more space and sites for highly dispersed Cu 2+ Provides abundant Lewis acid sites, ultimately forming a copper-ammine complex [Cu(NH 3 ) 4 ] 2+ , which can improve the Cu 2+ Utilization rate and NH 3 Adsorption capacity.
[0049] (2) The present invention adopts acid-modified activated carbon to obtain modified activated carbon with higher porosity and larger pores, which provides space for the subsequent loading of active components. At the same time, the acid solution also introduces carboxyl acid functional groups into the activated carbon, which are beneficial to the NH 3 The adsorption of activated carbon can improve the adsorption of NH 3The present invention uses ball milling to load the copper source onto the modified activated carbon. Compared with the traditional liquid phase impregnation method, the ball milling method of the present invention has a simple preparation process, does not require high-temperature calcination, and has low cost.
[0050] (3) The activated carbon material provided by the present invention has excellent NH 3 It has good adsorption performance and can be widely used in the efficient purification of ammonia in various gas sources. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is the N of the activated carbon materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. 2 Adsorption-desorption isotherms;
[0052] Figure 2 is a pore size distribution diagram of the activated carbon materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention;
[0053] Figure 3 is the NH of the activated carbon material prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. 3 Adsorption capacity diagram. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0055] In the following examples and comparative examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0056] Example 1
[0057] This embodiment provides an activated carbon material, which includes a modified activated carbon having a carboxyl functional group on its surface and an active component loaded on the modified activated carbon, wherein the active component includes copper chloride; the specific surface area of the activated carbon material is 289.92 m 2 / g; based on the total mass of the activated carbon material being 100wt%, the mass fraction of the active component is 5wt%;
[0058] The method for preparing the activated carbon material provided in this embodiment comprises the following steps:
[0059] (1) nitric acid with a concentration of 20% and activated carbon were mixed according to 100 mL:5 g, reacted at 50° C. for 10 h, filtered, washed with water until the filtrate was neutral, and dried at 80° C. for 15 h to obtain modified activated carbon;
[0060] (2) mixing copper chloride and modified activated carbon, ball milling them at 400 rpm for 2 h at a ball-to-material ratio of 1:1, and drying them at 80° C. for 15 h to obtain the activated carbon material.
[0061] The N of the activated carbon material prepared 2 Adsorption-desorption isotherms are shown in Figure 1 As shown, from Figure 1 It can be seen that according to the classification of the International Union of Pure and Applied Chemistry, all samples present type I and type IV composite isotherms, which are the characteristics of microporous and mesoporous structures. 3 After treatment, activated carbon has 2 The adsorption capacity was significantly improved.
[0062] The pore size distribution of the prepared activated carbon material is shown in Figure 2 As shown, from Figure 2 It can be seen that the pore size ranges of the four samples are consistent, while the pore size ranges of the four samples are consistent with those of the HNO 3 After treatment, the pore volumes in different pore size ranges increased significantly.
[0063] The NH 3 Adsorption capacity Figure 3 As shown, from Figure 3 It can be seen that after the activated carbon is treated with nitric acid, when the content of active components is only 5%, its NH 3 The adsorption capacity is 3.3 times that of the activated carbon without nitric acid treatment and without Cu loading. In other words, the adsorption capacity of activated carbon with 20% HNO 3 Simple treatment can significantly improve the utilization efficiency of low-loading Cu (5%).
[0064] Example 2
[0065] This embodiment provides an activated carbon material, which includes a modified activated carbon having a carboxyl functional group on its surface and an active component loaded on the modified activated carbon, wherein the active component includes copper chloride; the specific surface area of the activated carbon material is 607.66 m 2 / g; based on the total mass of the activated carbon material being 100wt%, the mass fraction of the active component is 2wt%;
[0066] The method for preparing the activated carbon material provided in this embodiment comprises the following steps:
[0067] (1) 200 mL:2.5 g of nitric acid with a concentration of 25% and activated carbon were mixed, reacted at 50° C. for 10 h, filtered, washed with water until the filtrate was neutral, and dried at 80° C. for 15 h to obtain modified activated carbon;
[0068] (2) mixing copper chloride and modified activated carbon, ball milling them at 300 rpm for 3 h at a ball-to-material ratio of 1:1.2, and drying them at 70° C. for 24 h to obtain the activated carbon material.
[0069] Example 3
[0070] This embodiment provides an activated carbon material, which includes a modified activated carbon having a carboxyl functional group on its surface and an active component loaded on the modified activated carbon, wherein the active component includes copper nitrate; the specific surface area of the activated carbon material is 180.70 m 2 / g; based on the total mass of the activated carbon material being 100wt%, the mass fraction of the active component is 4wt%;
[0071] The method for preparing the activated carbon material provided in this embodiment comprises the following steps:
[0072] (1) 30% nitric acid and activated carbon were mixed according to 100 mL:5 g, reacted at 50 ° C for 10 h, filtered, washed with water until the filtrate was neutral, and dried at 80 ° C for 15 h to obtain modified activated carbon;
[0073] (2) mixing copper chloride and modified activated carbon, ball milling at 500 rpm for 1 h at a ball-to-material ratio of 1:1.5, and drying at 80° C. for 10 h to obtain the activated carbon material.
[0074] Example 4
[0075] This embodiment provides an activated carbon material, which is different from Embodiment 1 only in that, when preparing the activated carbon material, the concentration of nitric acid in step (1) is 10%.
[0076] Example 5
[0077] This embodiment provides an activated carbon material, which is different from Embodiment 1 only in that, when preparing the activated carbon material, the concentration of nitric acid in step (1) is 40%.
[0078] Example 6
[0079] This embodiment provides an activated carbon material, which is different from Embodiment 1 in that, based on the total mass of the activated carbon material being 100 wt %, the mass fraction of the active component is 40 wt %.
[0080] Example 7
[0081] This embodiment provides an activated carbon material, which is different from Embodiment 1 in that, based on the total mass of the activated carbon material being 100 wt %, the mass fraction of the active component is 0.5 wt %.
[0082] Comparative Example 1
[0083] This comparative example provides an activated carbon material, which is not treated with nitric acid and is not loaded with copper chloride.
[0084] Comparative Example 2
[0085] This comparative example provides an activated carbon material, which is different from Example 1 only in that when preparing the activated carbon material, the modified activated carbon material does not undergo step (2), that is, it is not loaded with copper chloride.
[0086] Comparative Example 3
[0087] This comparative example provides an activated carbon material, which is different from Example 1 only in that when preparing the activated carbon material, the activated carbon is not subjected to the modification treatment of step (1).
[0088] Activity evaluation: The content of divalent copper salt in the prepared activated carbon material is obtained by ICP (inductively coupled plasma) testing, which refers to inductively coupled plasma technology, which is an important means for qualitative and quantitative analysis of trace metal elements and some non-metallic elements.
[0089] The dynamic adsorption capacity was tested in a plug flow reactor (6 mm in diameter). The reaction gas passed through the adsorbent once. The mass of the adsorbent was 100 mg. The initial atmosphere composition was (300 ppm ammonia, 70% relative humidity, 20% oxygen, nitrogen balance, gas flow rate of 100 mL / min); the test temperature was 25 °C; the test pressure was one atmosphere. When the outlet gas contained NH 3 When the concentration reaches 30 ppm, it is considered as breakthrough, and the adsorption curve is integrated based on the breakthrough time to calculate NH 3 Adsorption capacity. The activated carbon materials prepared in the examples and comparative examples were tested, and the test results are shown in Table 1 below.
[0090] Table 1
[0091]
[0092]
[0093] The test results show that:
[0094] (1) It can be seen from Examples 1 to 3 that the present invention uses modified activated carbon with a high specific surface area as a carrier. The modified activated carbon has a porous structure and can be used for Cu 2+ The loading provides more space and sites for highly dispersed Cu 2+ Provides abundant Lewis acid sites, ultimately forming a copper-ammine complex [Cu(NH 3 ) 4] 2+ , which can improve the Cu 2+ Utilization rate and NH 3 The preparation method of the present invention is simple and low in cost, and the activated carbon material provided has excellent NH 3 It has good adsorption performance and can be widely used in the efficient purification of ammonia in various gas sources.
[0095] (2) By comparing Example 1 with Example 4-Example 5, it can be seen that the present invention further controls the mass concentration of the acid solution to be 10%-40%. The concentration of the acid solution affects the specific surface area and the content of functional groups of the modified activated carbon. If the concentration of the acid solution is too low, the modification of the pore size of the activated carbon is limited; if the concentration of the acid solution is too high, the prepared activated carbon material has a poor NH 3 The adsorption capacity is no longer increased.
[0096] (3) By comparing Example 1 with Example 6-Example 7, it can be seen that the present invention further controls the content of the active component to be 1wt%-5wt%. The content of the active component affects the adsorption capacity of the adsorbent; if the content of the active component is too low, the ammonia adsorption capacity is too low; if the content of the active component is too high, on the one hand, the excessive active component will block the pores of the activated carbon, reduce the specific surface area and pore size of the activated carbon material, and reduce the Cu 2+ Dispersion, Cu 2+ The utilization rate of the active component is reduced, which is almost not improved compared with the activated carbon loaded with 40% copper source (88.63 mg / g) that has not been treated with nitric acid. On the other hand, it will cause a significant increase in production costs, which is not conducive to actual industrial production. Therefore, the content of the active component in the present invention is controlled to be 1wt%-5wt% to maximize the improvement of Cu 2+ The utilization rate is high, and the comprehensive effect of the activated carbon material provided by the present invention is more excellent.
[0097] (4) It can be seen from Example 1 and Comparative Example 1 that the adsorption capacity of the active agent that has not been treated with nitric acid and has not been loaded with copper chloride is very low and can be almost ignored.
[0098] (5) It can be seen from Example 1 and Comparative Example 2 that the adsorption capacity of the two is very different. This is because the Cu loaded after acid treatment 2+ , which promotes Cu 2+ Highly dispersed, improved Cu 2+ The utilization rate not only reduces the manufacturing cost, but also increases the adsorption sites and improves the adsorption capacity.
[0099] In summary, the present invention uses modified activated carbon with a high specific surface area as a carrier, and the modified activated carbon has a porous structure and can be used for Cu 2+ The loading provides more space and sites for highly dispersed Cu2+ Provides abundant Lewis acid sites, ultimately forming a copper-ammine complex [Cu(NH 3 ) 4 ] 2+ , which can improve the Cu 2+ Utilization rate and NH 3 The preparation method of the present invention is simple and low in cost, and the activated carbon material provided has excellent NH 3 It has good adsorption performance and can be widely used in the efficient purification of ammonia in various gas sources.
[0100] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. An activated carbon material, characterized in that: The activated carbon material includes modified activated carbon and an active component loaded on the modified activated carbon, and the active component includes a divalent copper salt; The surface of the modified activated carbon contains carboxyl functional groups, and the specific surface area of the activated carbon material is 50m 2 / g-550m 2 / g.
2. The activated carbon material according to claim 1, characterized in that The specific surface area of the activated carbon material is 270 m 2 / g-320m 2 / g; Preferably, based on 100 wt% of the total mass of the activated carbon material, the mass fraction of the active component is 1 wt%-5 wt%, preferably 3 wt%-5 wt%.
3. A method for preparing the activated carbon material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The acid solution is mixed with the activated carbon to obtain modified activated carbon after reaction; the copper source and the modified activated carbon are ball-milled and mixed to obtain the activated carbon material.
4. The preparation method according to claim 3, characterized in that: The mass concentration of the acid solution is 10%-40%, preferably 20%-30%; Preferably, the ratio of the volume of the acid solution to the mass of the activated carbon is (50-200) mL: (1-5) g; Preferably, the acid solution comprises any one of hydrochloric acid, sulfuric acid or nitric acid or a combination of at least two thereof, preferably nitric acid; Preferably, the mesh size of the activated carbon is 40-60 mesh; Preferably, the reaction is carried out under stirring; Preferably, the stirring speed is 300 rpm-600 rpm.
5. The preparation method according to claim 3 or 4, characterized in that: The reaction temperature is 40°C-60°C; Preferably, the reaction time is 12h-20h.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The copper source includes a divalent copper salt and / or a hydrate of a divalent copper salt; Preferably, the divalent copper salt includes any one of copper chloride, copper nitrate, copper sulfate or copper acetate, or a combination of at least two thereof, preferably copper chloride.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The ball-to-material ratio of the ball mill is 1:(1-2); Preferably, the rotation speed of the ball mill is 300rpm-500rpm; Preferably, the ball milling time is 1h-3h; Preferably, the diameter of the large ball used in the ball milling process is 1 cm-1.5 cm, and the diameter of the small ball is 6 mm-8 mm; Preferably, the mass ratio of large balls to small balls used in the ball milling process is 1:(1-2).
8. The preparation method according to any one of claims 3 to 7, characterized in that: After the ball milling, drying is also performed before obtaining the activated carbon material; Preferably, the drying temperature is 70°C-90°C; Preferably, the drying time is 12h-24h.
9. The preparation method according to any one of claims 3 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing nitric acid and activated carbon at a concentration of 20%-30% according to (50-200) mL: (1-5) g, reacting at 40° C.-60° C. for 12 h-20 h, filtering, washing with water until the filtrate is neutral, and drying at 70° C.-90° C. for 12 h-24 h to obtain modified activated carbon; (2) mixing cupric chloride and modified activated carbon, ball milling at 300 rpm-500 rpm for 1 h-3 h according to a ball-to-material ratio of 1:(1-2), and drying at 70° C.-90° C. for 12 h-24 h to obtain the activated carbon material.
10. A use of the activated carbon material as claimed in claim 1 or 2, characterized in that: The activated carbon material is used for ammonia adsorption.
Citation Information
Patent Citations
Preparation method of charcoal ammonia adsorbent
CN111821950A
A method for preparing modified activated carbon for ammonia adsorption
CN116002684B